STRATEGI MANAJEMEN KOMUNIKASI DALAM MENGHADAPI KRISIS KEPERCAYAAN MASYARAKAT TERHADAP RENDAHNYA KUALITAS PELAYANAN RUMAH SAKIT PEMERINTAH (STUDI: KUALITAS PELAYANAN KESEHATAN PADA RSUD SAWAHLUNTO) - EMI HANDRINA (LPPM STISIP IMAM BONJOL, 2022)
Trust in the context of communication is the picture of an expectation that words, promises, oral or written statements from another individual or group can be trusted. In organizations or institutions, trust is the most important capital in its survival. Organizations or institutions will not be able to survive long if they do not gain the trust of the public. This public trust will be one of the factors in the crisis. For this reason, it is considered very important for communication strategies in dealing with crises that occur in institutions and organizations. The crisis of trust experienced by most government hospitals on the quality of health services has an impact on the existence and existence of Sawahlunto Hospital which in fact is also the essence of public health services in Sawahlunto City. With the proliferation of the growth of competitors such as clinics and private hospitals, this is used as a benchmark for improving the quality of service that is sustainable. The tendency of the community to prefer clinics, private hospitals or in extreme conditions of treatment abroad, this is evidence that government hospitals have begun to be abandoned by the community in entrusting their health. The communication strategy of government hospital public relations practitioners must be able to overcome this so as not to cause a broad impact on the continuity of health institutions in Indonesia